Biotransport of persistent organic pollutants in the southern Hemisphere by invasive Chinook salmon (Oncorhynchus tshawytscha) in the rivers of northern Chilean Patagonia, a UNESCO biosphere reserve - Mónica Montory; Evelyn Habit; Pilar Fernandez; Joan O. Grimalt; Alan S. Kolok; Ricardo O. Barra; Javier Ferrer (Environment International, 2020)
Biotransport is often associated with migration patterns of species, including large, anadromous salmonids. Several studies have reported biotransport of persistent organic pollutants in the Northern Hemisphere, but there is no published information on biotransport ocurring south of the equator. Chile’s Patagonia is one of the last largely intact natural areas in the world. The objective of this study was to determine whether persistent organic pollutants are transported by the invasive Pacific Chinook salmon (O. tshawytscha) from the Pacific Ocean to Chilean Patagonia. Samples of juvenile and adult Chinook salmon were analyzed for polychlorinated biphenyls, pesticides and polybrominated diphenyl ethers. The results revealed that concentrations of POPs in adults migrating into Patagonian rivers were significantly higher than those found in juveniles migrating seaward. A mass balance analysis indicates that Chinook salmon are a source of persistent organic pollutants to Chilean Patagonia inland waters.Capsule: Biotransport of Persistent Organic Pollutants (POPs) by Chinook salmon (O. tshawytscha) from the Pacific Ocean to Chilean Patagonia has been confirmed by mass balance of POPs.